2014
DOI: 10.1097/eja.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

The LMA-Supreme versus the I-gel in simulated difficult airway in children

Abstract: In the simulated difficult airway in children, both airway devices provided effective ventilation. Paediatric size 2 LMA-S sustained a higher airway pressure before leaking and was quicker to insert than the I-gel equivalent. These differences may not be clinically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
4
18
1
Order By: Relevance
“…The initial airway leak pressures in this study for the AuraGain are similar to previous studies with the LMA Supreme [1,5,6,12], but slightly lower than the reported airway leak pressures of the LMA ProSeal [2,13] and i-gel [14][15][16] in children. The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance.…”
Section: Discussionsupporting
confidence: 87%
“…The initial airway leak pressures in this study for the AuraGain are similar to previous studies with the LMA Supreme [1,5,6,12], but slightly lower than the reported airway leak pressures of the LMA ProSeal [2,13] and i-gel [14][15][16] in children. The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance.…”
Section: Discussionsupporting
confidence: 87%
“…12 In a study simulating a difficult airway scenario, the LMA Supreme was associated with higher leak pressures than the i-gel. 13 To date, there are only a limited number of studies that assessed the clinical performance of the LMA Supreme in infants.…”
Section: Basic Sga Insertion Techniquesmentioning
confidence: 99%
“…Several studies have shown that its airway leak pressures are higher than the LMA Classic, ProSeal, and Supreme. 13,22 Some clinicians have reported technical difficulties with its use, such as spontaneous displacement after insertion requiring additional positional adjustments, especially in smaller children. In a recent metaanalysis, a notable advantage of the i-gel was its higher airway leak pressures and better fiberoptic views compared with other SGAs in children.…”
Section: I-gelmentioning
confidence: 99%
“…A number of randomised trials have compared the i‐gel with the most commonly used supraglottic airway device, the laryngeal mask, in its different variations . However, published studies are inconclusive with regard to oropharyngeal leak pressure; some studies have found that the i‐gel provides a higher leak pressure , whereas others conclude that the i‐gel offers lower , or equivalent, leak pressures . In addition, some of these studies describe practices that are not routine, such as the use of neuromuscular blocking drugs in conjunction with positive pressure ventilation .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the majority of studies comparing the i‐gel with laryngeal masks, the laryngeal mask cuff was not inflated optimally. In particular, both hyperinflation of the cuff (with measured intracuff pressures above 40 cmH 2 O) and inflation by volume without the use of cuff pressure monitoring (which has been associated with hyperinflation ) commonly occurred. It has been demonstrated that inflation to an intracuff pressure above 40 cmH 2 O is associated with greater leakage and increased morbidity .…”
Section: Introductionmentioning
confidence: 99%